Uterine rupture: review of cases from tertiary care centre in India - Paprikar, Sachin; Lagoo, Arpita; Lagoo, Jyoti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Uterine rupture is rare catastrophic complication associated with high incidence of maternal and perinatal morbidity and mortality. This study aimed at assessing the incidence of uterine rupture; maternal and fetal outcomes in cases of uterine rupture and factors associated with it. Methods: This retrospective study was carried out in the department of obstetrics and gynaecology, Late Baliram Kashyap memorial government medical college and Shaheed Mahendra Karma memorial hospital, Bastar, Chhattisgarh, India. All the cases of rupture uterus, who were admitted with the diagnosis or who had rupture during their stay in our hospital during the study duration of July 2018 to March 2020 were included in our study- 37 cases. Results: Out of 37 cases of ruptured uterus 8 rupture occurred in women with prior lower segment caesarean section (LSCS) and 29 occurred in women without prior LSCS. There were equal numbers of cases (17 cases each, 45.9%) in the age groups 25-30 years and 31 years and above. Incidence of rupture was highest in multiparous (3 and above). 70.3% of rupture were un-booked patients. 89.2% were referred from periphery. 86.5% of ruptures occurred at more than 37 weeks. 54% of rupture had of inter pregnancy interval of less than 24 months. Most common predisposing factor for uterine rupture in our study was obstructed labor. The most common site of rupture was found to be anterior surface of lower segment of uterus. Maternal morbidities seen include need for blood transfusion in 94.5% of cases. Among the maternal morbidities noted, severe anemia requiring blood transfusion was most commonly observed. Conclusions: Rupture of the pregnant uterus should be looked as a preventable entity. All possible efforts to reduce the incidence and the resultant maternal morbidity and mortality due to uterine rupture should be undertaken.